2014
DOI: 10.1086/674632
|View full text |Cite
|
Sign up to set email alerts
|

Omnivory and opportunism characterize food webs in a large dry-tropics river system

Abstract: We analyzed basal sources, trophic levels, and connectance in dry-season food webs on 4 rivers in the upper Burdekin catchment in the dry tropics of northeastern Australia. The region is characterized by episodic summer rainfall, and most of the annual river flow occurs in a short period. In the dry season, rivers typically contract into a series of water holes of varying permanence and hydrologic connectivity. We used stable-isotope and stomach-content analyses to identify trophic levels of macroinvertebrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 90 publications
(145 reference statements)
2
35
0
5
Order By: Relevance
“…High hydrologic variability has been shown to correspond to a generalist pattern of feeding ecology among fishes (Poff and Allan , Blanchette et al. ) and may be a key factor mediating the trophic ecology and resultant foodweb structure associated with fish assemblages (Winemiller and Rose , Winemiller , Mims and Olden ), particularly those of the desert southwest of the United States (Olden et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High hydrologic variability has been shown to correspond to a generalist pattern of feeding ecology among fishes (Poff and Allan , Blanchette et al. ) and may be a key factor mediating the trophic ecology and resultant foodweb structure associated with fish assemblages (Winemiller and Rose , Winemiller , Mims and Olden ), particularly those of the desert southwest of the United States (Olden et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work utilizing stable isotope techniques has indicated terrestrial resources can be important contributions to food webs in some arid streams and rivers and that this integration may be mediated by seasonal and hydrologic variability (Zeug and Winemiller , Blanchette et al. , Sabo et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that combined different approaches such as stable isotope and gut content analyses also show considerable dietary variation within taxa among sites, and concluded that omnivory and opportunistic feeding were widespread (e.g. Blanchette et al., ; Paice et al., ). Furthermore, our study showed that dissimilarities among the diet of each taxon at each site were not explained by the availability of trophic resources.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have proposed that the present dominance of omnivorous species within the Amazon Basin may be an evolutionary response to the large diversity of food items and to the seasonality of their abundance and availability (Lowe-McConnell, 1999;Mérona and Rankin-de-Mérona, 2004;Blanchette et al, 2014). An extreme drought could result in a severe deterioration of the water quality, with high temperature and low dissolved oxygen, which would in turn have negative consequences for the quality of their food sources.…”
Section: Discussionmentioning
confidence: 99%